Tai-chi-chuan and yoga onpostexercise hypotension: comparison to aerobic and resistance exercise - João Douglas Alves; Jorge Luiz de Brito Gomes; Caio Victor Coutinho de Oliveira; José Victor de Miranda Henriques Alves; Fabiana Ranielle de Siqueira Nogueira; Aline de Freitas Brito
Abstract Introduction: Tai-Chi-Chuan and Yoga have becoming popular practices. However is unclear the cardiovascular effects, and if they present similar behavior to aerobic and resistance sessions. Objective: To evaluate the cardiovascular responses during the session and post-exercise hypotension (PEH) of Tai Chi Chuan (TS) and Yoga (YS) in comparison to aerobic (AS) and resistance (SR) exercises. Methods: Fourteen young women (22.3 ± 2 years) apparently healthy performed four sessions (AS, RS, TS and YS). The heart rate (HR), systolic (SBP) and diastolic blood pressure (DBP) were recorded at resting, during (every 10 minutes) and until 50 minutes of recovery. Results: AS, RS, TS e YS showed significant increase in HR compared to resting.AS at 10, 30 e 50 minutes in relation to RS, TS e YS. The RS in relation to TS and YS at 10, 30 and 50 minutes. No significant difference between TS and YS. SBP was significantly increased in AS, RS, TS e YS at 10, 30 e 50 minutes during the session, in relation to rest. AS was significantly higher at 30 e 50 minutes than RS and higher than TS and YS at 10, 30 e 50 minutes. No significant difference in DBP. For PEH, AS, RS and TS significantly reduced at 10, 30 and 50 minutes. YS reduced at 50 minutes. No significant diastolic PEH. Conclusion: TS and YS showed as safe alternatives of exercising in the normotensive young adult woman, despite having lower values, they promote similar hemodynamic behavior to AS and RS.